Productive Waqf Model in Darunnajah Islamic Boarding School and its Development for Educational Institutions - Azizah Mursyidah; Miftahul Anwar (Journal of Noesantara Islamic Studies, 2024)
This research focuses on the productive waqf model in Islamic Boarding School Darunnajah and its impact on the development of educational institutions. Islamic Boarding School Darunnajah, as one of the leading Islamic educational institutions in Indonesia, has adopted various productive waqf models to improve its financial sustainability and infrastructure development. This research aims to analyze the various productive waqf models implemented in Islamic Boarding School Darunnajah, evaluate their effectiveness in supporting the sustainability and improvement of education quality, and formulate recommendations for further development. Using a qualitative approach, data was collected through interviews with Islamic Boarding School managers, field observations, and analysis of relevant documents. The results show that Islamic Boarding School Darunnajah has successfully implemented various productive waqf models, including agricultural land management, commercial property, and financial investment. These models have contributed significantly to increasing the Islamic Boarding School’s income and supporting the development of various educational programs. Based on the findings, this study recommends measures to improve the implementation of productive waqf in Islamic Boarding School Darunnajah, including increased cooperation with the government and the private sector, the development of training programs for Islamic Boarding School managers, and the establishment of strategic partnerships with financial and investment institutions. As such, this study contributes to the understanding of productive waqf practices in Islamic Boarding Schools and offers valuable insights for other Islamic educational institutions interested in developing similar models. The practical implications of this research may help in improving the financial sustainability and quality of education in Islamic Boarding School as well as other Islamic educational institutions in Indonesia.